Transnational Experiences - Rasmussen, Lene Kofoed; Galal, Lise Paulsen (Women, Gender & Research, 2007)
Globalisation, migration and modern technology mean that it is possible to talk about today’s society as stretching beyond the borders of nation states. Is this basic insight of transnational studies also valid if the borders are those of a predominantly Muslim Middle East and an increasingly migrant-hostile Europe? If so, what features does the transnational experience of Middle Eastern migrants in Europe have? A number of scholars set out to investigate these questions in a research seminar in September 2006. Gender negotiations and expectations appeared to be central to the transnational experience and was addressed in most of the papers presented at the seminar. Thus the journal Women, Gender and Research (Kvinder, Køn og Forskning) provides an apt arena for taking these questions further. In this special issue of the journal, transnational experiences of families, individuals, networks and organisations are presented by some of the participants in the seminar and other invited contributors.